Surgical repair of sternum chondrosarcoma in a 58-year-old male patient: Case Report - González Ramírez, José Alberto (2020)
Sternum chondrosarcoma is an infrequent malignant neoplasm which occurs mainly in adults over 50 years old. Grade 1 chondrosarcoma is the most frequent among the heterogenous group of tumors that fall into this classification, however, it is most frequently presented in the pelvic region, in long bones of the appendicular skeleton and in the costal region. The fact that it presents in the sternal region compromises the constitution of nearby organs. Due to radiotherapy and chemotherapy having a scarce therapeutic effect, we proceeded with surgical intervention where a wide resection of the sternal chondrosarcoma and liver metastasectomy was performed, subsequently, the chest wall was rebuilt using titanium plates and microsurgical right dorsal muscle flap. The final result was favorable. We present a conventional chondrosarcoma (grade 1) case at the xyphoid process level with liver metastasis.